Adhesion of lunar simulant dust to materials under simulated lunar environment conditions. (October 2022) - Barker, Donald C.; Olivas, Andres; Farr, Ben; Wang, Xu; Buhler, Charlie R.; Wilson, Jeremy; Mai, John
Abstract: A test stand was designed to semi quantitively measure the adhesion of JSC-1/1A lunar simulant dust to materials proposed for use in the lunar surface environment. Sieved simulant <45 μm in diameter was uniformly deposited on sample surfaces. Dust adhesion was indicated as the centrifugal force created from rotation of the test stand to shed dust under high vacuum and UV exposure conditions The device generated a maximum centripetal force greater than 400 g's. Dust adhesion on aluminum, anodized aluminum, Ortho fabric and Z93P painted aluminum was observed and analyzed over a 12 step, increasing acceleration profile. At each rotation cycle, dust coverage was recorded using a camera and changes in the coverage were analyzed in post-processing to provide an indication of the adhesive force dust particles would have to overcome to be removed from the surface. Results showed that all material coverage amounts exhibited a similar shedding profile with individual plateaus occurring below 30 μm depending on material. Bare and anodized aluminum had higher adhesion values in vacuum than did the samples exposed to UV at high centripetal acceleration levels. The Z93P painted aluminum and Ortho fabric indicated the opposite, whereby UV exposed samples retained more dust at higher acceleration levels and thereby larger dust particles likely adhered to the surfaces. Ultimately, this testing indicates that the apparatus provides acceptable control and conditions to assess dust adhesion of lunar simulants. Increased precision can be attained by changes in lighting, camera orientation and clarity, and sample dust application. Highlights: Lunar dust adhesion was demonstrated using centripetal force measurement profile. Relevant adhesion measurements were obtained for materials on the lunar surface. Measured material adhesion differences between vacuum and vacuum with UV light.